Morpho-functional aspects of mutual influence of bronchial asthma and gastroesophageal reflux - R. I. Pleshko; I. V. Sukhodolo; L. M. Ogorodova; Ye. A. Gereng; L. I. Volkova; N. A. Krivova; G. M. Chernyavskaya; K. A. Nosenko (Бюллетень сибирской медицины, 2005)
Aimed at investigating pathomorphological aspects of mutual influence of bronchial asthma and gastroesophageal reflux (GER), gastrobioptates, bronchobioptates and bronchial mucus of bronchial asthma of 48 patients having GER and 55 patients not having it. Helicobacter inflammation and fundal stomach department mucous membrane atrophy (non-severe asthma) and using systemic corticosteroids (severe asthma) were shown to influence on GER forming. GER-positive patients revealed hyperproduction of dense bronchial mucus.